Hysterectomy with trans-cervical resection of a prolapsed submucosal fibroid: a challenging surgical approach - Dhandapani, Kalyani Sai; Sezhian, Varshini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Uterine fibroids or leiomyomas, are the common benign tumors of female reproductive tract that affects women of almost all age groups, leading to various gynecological problems such as heavy menstrual bleeding, dysmenorrhea, subfertility, and anemia. The increasing prevalence of these fibroids, due to prolonged estrogen exposure, influenced by lifestyle factors such as obesity, alcoholism, nulliparity and medical conditions like hypertension, have made necessitate their timely management to reduce significant morbidity. Surgical interventions, particularly hysterectomy, are considered definitive for women of perimenopausal and postmenopausal age group with symptomatic fibroids, though challenging due to the altered uterine anatomy. Here we present a case of a 46-year-old woman, P2L2, who reported with a history of heavy menstrual bleeding, dysmenorrhea, and intermenstrual bleeding, along with anemia (Hb 8.4 g/dL). Ultrasonography revealed a bulky uterus with multiple intramural fibroids and a prolapsed submucosal fibroid protruding through the cervical OS which bled on touch. She underwent a successful abdominal hysterectomy, with a unique surgical approach to manage the prolapsed submucosal fibroid. A vertical incision on the anterior cervix facilitated the clamping and removal of the pedunculated fibroid through the vagina, followed by its removal with minimal blood loss. This case highlights the importance of accurate preoperative imaging and surgical planning and use of surgical strategies such like this to improve operative outcomes and reduce morbidity, especially in anemic patients.